2000
DOI: 10.1103/physrevlett.85.2793
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Emission of Semiconductor Microcavities in the Strong Coupling Regime

Abstract: We report on the nonlinear laserlike emission from semiconductor microcavities in the strong coupling regime. Under resonant continuous wave excitation we observe a highly emissive state. The energy, dispersion, and spatial extent of this state is measured and is found to be dispersionless and spatially localized. This state coexists with luminescence that follows the usual cavity-polariton dispersion. It is attributed to the amplification of luminescence by a parametric gain due to cavity-polariton scattering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
91
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 16 publications
8
91
0
Order By: Relevance
“…The coherence of these beams was demonstrated by significant spectral narrowing, proving that they are due to a parametric process rather than resonantly enhanced incoherent photoluminescence. Houdré et al 6 , have also observed a nonlinear emission at 0 • for a structure pumped at 10 • . However, in this experiment the pair scattering resonance condition is not satisfied, suggesting that different physics may be involved.…”
mentioning
confidence: 91%
“…The coherence of these beams was demonstrated by significant spectral narrowing, proving that they are due to a parametric process rather than resonantly enhanced incoherent photoluminescence. Houdré et al 6 , have also observed a nonlinear emission at 0 • for a structure pumped at 10 • . However, in this experiment the pair scattering resonance condition is not satisfied, suggesting that different physics may be involved.…”
mentioning
confidence: 91%
“…3.3, we explain the necessity for carrying out a numerical analysis of the OPO. Much experimental work has been carried out on polaritons in the OPO regime [18,36,19,37,38,39,40,41,42,43,44,45] (for a review on the experiments, see Ref. [46]).…”
Section: Optical Parametric Oscillator Regimementioning
confidence: 99%
“…Polaritons in semiconductor microcavities are hybrid quasiparticles consisting of a superposition of cavity photons and two-dimensional collective electronic excitations (excitons) in an embedded quantum well [6]. Owing to their mutual Coulomb interaction, pump polaritons generated by a resonant optical excitation can scatter resonantly into pairs of polaritons (signal and idler) [7,8,9,10,11,12,13]. In the low excitation limit, the polariton parametric scattering is a spontaneous process driven by vacuum-field fluctuations [9] whereas, already at moderate excitation intensity, it displays self-stimulation [12].…”
mentioning
confidence: 99%